Jack's lemma for certain subclasses of analytic functions defined by a new fractional linear operator - Abdulnaby, Zainab Esa; Ibrahim, Rabha Waell; Kilicman, Adem (AIP Publishing, 2016)
The theory of functional operator has been employed in several areas of mathematics, especially in the geometric function theory in the open unit disk. By utilizing the Moment-Generating function, we define a new fractional linear operator in the open unit disk. We discuss some geometric properties of this operator on some subclasses by applying the concept Jack’s lemma.